Editorial: At the University and in the School. Tensions or Strategic Alliance? - Chávez Preisler, Carolina (2023)
This reflection deals with Initial Teacher Training and the importance of pedagogical practices. The reflection will be addressed in relation to three questions: How important are pedagogical practices in Initial Teacher Training?; What tensions are there in relation to pedagogical practices?; And what models of significant pedagogical practices exist?